About the Byzantine mime: Prodromus and his Amarantus (H 146) (Circe de clásicos y modernos, 2022)
It is presented here a Spanish version of the Prodromus’ text 146 Hörandner (xiith century), with footnotes and a study, on the basis of the Migliorini’s edition (2010) with some little modifications. It is postulated that this text is a literary mime, which performance was made in a social gathering, a Byzantine θέατρον.
Keywords: Byzantium; satyre; mime; Prodromus; Amarantus; marriage; philosophy